Pengaruh Daya Tarik Iklan, Pemilihan Lokasi Dan Electronic Word Of Mouth (E-Wom) Terhadap Minat Beli Unit Apartemen Gunawangsa Tidar Surabaya - Noer Faridatul Sholehah; Nur Farida; Nur Aini Anisa (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
The goal of this study is to ascertain the impact of advertising attraction location choice and electronic word of mouth (e-WOM) on interest in purchasing condominium units in Gunawangsa Tidar Surabaya. A quantitative approach is taken in this investigation. Source data were used, as well as questionnaires for data collecting. As can be observed from the results of the multiple linear regression analysis, the analytical findings of this study demonstrate that advertising attractiveness has a substantial impact on location choice and interest in purchasing an electronic word of mouth (e-WOM) unit. Y = 5.602 0.039 0.143 0.247 . According to the linear model, location preference and interest in purchasing electronic word of mouth (e-WOM) devices grow in response to favorable advertising.